An improved model to analyze radiative heat transfer in flame-resistant fabrics exposed to low-level radiation. Issue 16 (October 2017) - Su, Yun; He, Jiazhen; Li, Jun
An improved heat transfer model, based on the two-flux model, in a multilayer flame-resistant fabric system with an air gap was proposed. The developed model considered the thermal radiation by absorbing, transmitting, emitting and reflecting in porous fabrics. The predicted results of the new model were compared with the previous Beer's law model and the experimental results, and were found to be in good agreement with the experimental ones. The aim of this study is to investigate the mechanism of radiant heat transfer in the multilayer fabric system and the effects of the optical properties of flame-resistant fabric on heat transfer in the fabric system. The numerical results demonstrated that the self-emission in multilayer fabric system increases not only the rate of thermal energy transferred to human skin during thermal exposure, but also the rate of thermal energy transmitting to the ambience during cooling. The fabric's optical properties have a complex influence on the transmitted and stored energy in multilayer protective clothing. The finding obtained in this study can provide references for the improvement of the thermal protective performance of flame-resistant fabrics.